A study on the relationship between internet popularity and emotional perception of urban parks using Weibo data in Luoyang, China - Yipeng Ge; Yafei Guo; Yueshan Ma; Songjie Ma; Yang Liu; Xinjie Qin (Scientific Reports)
Abstract The role of Internet Popularity (INPY) in shaping public perception of urban parks is increasingly significant. Although existing studies have explored the impact of parks on public perception, they primarily focus on traditional environmental indicators (such as NDVI and GVI), overlooking the potential influence of INPY generated on social media on public emotions. This study aims to fill this gap by analyzing 41,675 social media data from Luoyang, China, quantifying emotional perception(ETPN), and using Multi-task and Hierarchical Linear regression models to explore the relationship between INPY, public perception, and urban parks. The results show: (1) INPY has varying degrees of positive influence on the Emotional Gradients (ETGD) from negative to positive, with the impact intensity increasing from low to high; (2) A 200-meter GVI is negatively correlated with negative emotions, whereas 500-meter and 1000-meter NDVI scales positively affect positive emotions; (3) Seasons affect emotional expression, particularly positive emotions. The study highlights that INPY mainly impacts positive emotions, while GVI and NDVI help mitigate negative emotions and enhance overall ETPN. These results provide urban planners with a new perspective on understanding the value of urban parks and offer scientific support for urban space optimization and policy-making.